Faktor- Faktor Yang Meningkatkan Keputusan Pembelian Produk oleh Generasi Milenial Pada Pasar Tradisional di Kota Kupang - Sain, Roswita Felsiani; Loinenak, Jeanet Jeshintya Sarce; Manikin, Albert Palla; Baso, Susana Purnamasari (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2025)
This research aims to analyze the factors that influence millennials' purchasing decisions in Kupang City's traditional markets. The main focus is to identify how marketing elements such as product, price, place, and promotion (4Ps) influence millennial consumer behavior in traditional markets. In this context, the right marketing strategy can help traditional market traders increase their appeal amid competition with modern markets and online shopping trends. This research uses quantitative methods with a Structural Equation Modeling (SEM) approach to analyze the data. The results of this study are expected to provide strategic recommendations to improve purchasing decisions by millennials, particularly in Kupang City's traditional markets.